Pengaruh Berbagai Jenis dan Volume Media Tanam terhadap Pertumbuhan dan Hasil Melon (Cucumis melo L.) dengan Sistem Hidroponik - Shendi Elendrya; Rizka Novi Sesanti; Lisa Erfa; Sismanto Sismanto; Nanang Wahyu Prajaka (Journal of Horticulture Production Technology, 2023)
Conventional melon cultivation has limiting factors, one of which is the extreme climate and the provision of sufficient nutrients that are not fully absorbed by plants, which results in greatly varied and inadequate of melon production. The purpose of this research was to determine the type of planting media, the volume of planting media, and combination between the type of planting media and the volume of planting media that was best for the growth and yield of melon plants in a hydroponic system. This research was conducted in the greenhouse of the Lampung State Polytechnic from March to June 2021. The analysis used was Factorial Randomized Block Design (RBD). The first factor was the type of planting media (husk charcoal+sand, cocopeat+sand, husk charcoal only, and cocopeat only). The second factor was the volume of the planting medium (4.3 liter, 7.5 liter, and 9.9 liter). In this study, there were 12 treatment combinations, 3 replications, and analyzed using 5% level of Tukey's test. The variables observed in this study were plant height, number of leaves, leaf width, pollination time, fruit weight, fruit diameter, and fruit flesh thickness. The results showed that the type of planting media, the volume of planting media, and the combination of both did not significantly have a different effect on the observed variables of the growth and yield of melon plants.